Learning anxiety in interactions with the outgroup: Towards a learning model of anxiety and stress in intergroup contact. (May 2016) - Paolini, Stefania; Harris, Nicholas C.; Griffin, Andrea S.
While "knowledge learning" about the outgroup has been regarded as one of the key mechanisms for the contact–prejudice relation since the contact hypothesis' first inception (Pettigrew & Tropp, 2008), "learning, " more broadly, has rarely been used as an explanatory framework to investigate the consequences of intergroup contact. In this article, we lay the foundation of a learning model of anxiety and stress in ingroup–outgroup interactions. We distinguish between episodic and chronic anxiety responses to the outgroup and recommend investigations on the complexities of their dynamic interplay, as individuals accumulate and dynamically integrate their experiences with the outgroup over time. Through a review of established and emerging psychophysiological and behavioral research of anxiety during ingroup–outgroup interactions, we identify evidence consistent with this dynamic outlook of intergroup contact effects. In this context, we also advance novel and untested predictions for future investigations onto the temporal integration of contact effects during an individual's lifespan.